Do sticky wages matter? New evidence from matched firm-survey and register data - Anne Kathrin Funk; Daniel Kaufmann (ETH Zurich, KOF Swiss Economic Institute, 2020)
This paper provides novel evidence on downward nominal wage rigidities and their allocative effects in Switzerland. We match individual wages from a bi-annual firm survey with information on annual income and employment from social security register data. We find relevant downward nominal wage rigidities in the base wage, which accounts for more than 90% of employment income. We then identify the allocative effects of downward nominal wage rigidities on income and employment after an unexpected 1% decline of the consumer price level. Base wage rigidities cause a decline of aggregate income (-0.39%) and employment income (-0.97%), as well as an increase of unemployment (2.11%).
hdl:20.500.11850/420479
Keywords: E30; E40; E50; 330; Downward nominal wage rigidity; income; unemployment; deflation